The Mediating Role of Job Satisfaction in the Relationship Between Self-Efficacy, Digital Competence, and Early Childhood Daycare Service Quality in Depok City - Yulismar Yulismar; Lili Nurlaili; Saiful Anwar; Siti Zubaidah (Sultan Publisher, 2026)
The quality of educational services in daycare institutions has become increasingly important as urban families increasingly rely on professional early childhood care services. Despite the growing literature on teacher competencies and organizational outcomes, empirical studies integrating psychological, technological, and organizational dimensions within daycare institutions remain limited. This study aims to examine the effects of self-efficacy and digital competence on service quality through the mediating role of job satisfaction among daycare teachers in Depok City, Indonesia. A quantitative explanatory design was employed using survey data collected from 146 teachers working in registered daycare institutions. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS software. The results indicate that self-efficacy positively affects job satisfaction (β = 0.381, p < 0.001) and service quality (β = 0.291, p < 0.001), while digital competence positively influences job satisfaction (β = 0.427, p < 0.001) and service quality (β = 0.318, p < 0.001). Job satisfaction also exerts a significant positive effect on service quality (β = 0.356, p < 0.001) and partially mediates the relationships between teacher competencies and service quality. The model explains 62.4% of the variance in job satisfaction and 71.0% of the variance in service quality. These findings suggest that improving daycare service quality requires not only strengthening teachers' professional and technological capabilities but also enhancing workplace well-being and organizational support. This study contributes to the literature by integrating psychological, technological, and organizational perspectives within a single framework and by providing empirical evidence from the context of early childhood daycare institutions in Indonesia.